Orbital IgG4 Disease: Imaging Findings on 68Ga-DOTANOC PET/CT - Arora, Saurabh (Nucl Med Mol Imaging, 2019)
Immunoglobulin G4 (IgG4)–related diseases are a spectrum of systemic inflammatory conditions of unknown etiology, which are characterized by infiltration of tissues by IgG4 plasma cells and sclerosing inflammation (Cheuk and Chan Adv Anat Pathol 17:303–32, 2010). Although this condition was initially described in relation to autoimmune pancreatitis, now it has been reported in almost every organ system of body (Zen and Nakanuma Am J Surg Pathol 34:1812–9, 2010, Masaki et al. Ann Rheuma Dis 68:1310–5, 2009). Orbital involvement by IgG4 disease can involve extraocular muscles (EOM), lacrimal glands, conjunctiva, eyelids, infraorbital nerve, orbital fat, and nasolacrimal system (McNab and McKelvie. Ophthal Plast Reconstr Surg 31:167–78, 2015, Katsura et al. Neuroradiology 54:873–82, 2012). The basis of using (68)Ga-DOTANOC PET/CT in IgG4 orbital disease is the known expression of somatostatin receptors in chronic inflammatory cells (Cuccurullo et al. Indian J Radiol Imaging 27:509-16, 2017) and also avidity shown previously in other IgG4-related diseases (Cheng et al. Clin Nucl Med 43:773-6, 2018).